Penggunaan Media Ajar Digital Berbasis Deep Learning dalam Evaluasi Pembelajaran PAI di Sekolah Dasar - Azizah, Kamilatin; Qomariyah, Nurul; Listiana, Heni (Lembaga Peneltian Universitas Islam Internasional Darullughah Wadda'wah, 2025)
The advancement of technology and the implementation of the Merdeka Curriculum necessitate innovation in the learning process, particularly in Islamic Religious Education (PAI) at the elementary school level. The deep learning approach, which emphasizes deep understanding, critical thinking, and practical application, aligns well with the characteristics of the Merdeka Curriculum. This study aims to develop digital learning media based on deep learning and examine its effectiveness in evaluating PAI learning. The research method used is Research and Development (R&D) with the ADDIE development model (Analyze, Design, Develop, Implement, Evaluate). The research subjects were fifth-grade students at SDN Larangan Tokol 4. The developed products include an interactive e-book featuring stories of the Prophet's companions and a digital crossword puzzle (e-puzzle), designed according to the deep learning principles of mindful, meaningful, and joyful. The results show that the digital media successfully increased student engagement, improved learning outcomes, and facilitated a more effective and enjoyable evaluation process. The implementation also promoted cognitive development from the application level (C3) to the analysis level (C4). Despite technical limitations in digital evaluation, the results indicate a significant improvement in students' comprehension. This study is important as it demonstrates that integrating digital learning media based on deep learning can support more contextual, interactive, and meaningful PAI learning. These findings provide a foundation for developing similar